Повесть о рыжей девочке - Будогоская Лидия Анатольевна (Вот как это было, 2016)
Экземпляры: ф.18 (20180529) / Инвентарный номер: 2969 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Б 90 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44